Misoprostol vaginal insert (Mysodelle) versus Dinoprostone intravaginal gel (Prostin) for induction of labour. (September 2019) - Sharp, A.; Faluyi, D.; Alfirevic, Z.
Abstract: Objective: The aim of this study is the compare the effectiveness and safety of Misoprostol Vaginal Insert (Mysodelle) versus Dinoprostone intravaginal gel (Prostin) for induction of labour. Study design: We performed a prospective cohort study of the use of misoprostol vaginal inserts (Mysodelle) in the induction of pregnancy and compared it to a historical cohort of women induced with the Dinoprostone intravaginal gel (Prostin) at the Liverpool Women's Hospital, a large UK teaching hospital. Results: A total of 4102 women were induced between December 2016 and September 2018 of whom 2540 were induced with dinoprostone gel until September 2017. Since October 2017 1562 were induced using misoprostol vaginal inserts (MVI). The MVI demonstrated a significantly quicker median time to delivery compared with dinoprostone gel (18.2 h versus 21.8 h; p < 0.0001). There was a 32% reduced risk of Caesarean section with MVI (7.5% vs 10.9%; RR 0.62 95%CI 0.56–0.84) There was no significant difference in any of the key maternal or neonatal adverse outcomes. Conclusions: The results of this study suggest that misoprostol vaginal inserts, compared with dinoprostone intravaginal gel, achieve quicker delivery times, and a reduction in caesarean sections with no increased rate of adverse maternal or neonatal outcomes.